EURASIAN GEOGRAPHICAL CHARACTERISTICS OF THE BALKAN PENINSULA AS A FRAMEWORK FOR GEOPOLITICAL PROCESSES - Mujević, Demir (Political Review, 2026)
The Balkans’ geographic position at the crossroads of Europe, Asia, and Africa makes it a key geopolitical hub. The subject of this paper is the analysis of the Eurasian geographical characteristics of the Balkan Peninsula and their repercussions on the geopolitics of major world powers (USA, Russia, EU, China) and powerful regional actors in the Balkan Peninsula, without a detailed examination of the individual and mutual geopolitical relations of the Balkan countries themselves. Through the lens of balkanization, this study investigates how geographical and political differences in the Balkans shape its history and contemporary geopolitical relations. Some of the historical geopolitical processes that dominantly shaped the Balkans include the influence of the Ottoman Empire and the breakup of Yugoslavia. Contemporary geopolitical processes  in  the Balkans, with a focus on NATO and EU integration, demonstrate how geographical features and the strategic interests of major powers (especially the USA and Russia) shape the region. At the end, the possibilities for preserving stability, fostering further connections, and shaping the region’s perspective are considered, which are directly related to the Balkans’ geographical and strategic position in the Eurasian context.
Keywords: Eurasian characteristics; Balkan Peninsula; geopolitical processes; Balkanization